Burning up on Reentry: The Effect of Entrepreneurial Exit in the Hiring Context - Waddingham, Jacob A.; Zachary, Miles A.; Walker, H. Jack (Journal of Management, 2024)
A great deal of research on entrepreneurial exit focuses on the potential challenges entrepreneurs may face when launching a new venture, but very little is known about those who choose to re-enter the traditional workforce. It is commonly assumed that an entrepreneur can always “go back to work,” however, it is unclear how recruiters evaluate entrepreneurial experience early in the selection process. Drawing from screening theory, attribution theory, and the person-organization fit perspective, we designed three studies to begin answering questions about the challenges former entrepreneurs may face when attempting to find more traditional employment. Study 1 revealed that recruiters evaluate former entrepreneurs more negatively than job applicants with more traditional work experience, and this relationship is stronger when former entrepreneurs close—versus sell—their venture. Study 2 employed a qualitative, inductive approach to examine why recruiters may be biased against former entrepreneurs and found that there are often assumptions of rapid turnover, insubordinate behavior, and organizational misfit. Finally, the Study 3 results suggested that the negative evaluation of former entrepreneurs may not be universal and depends on important contextual factors such as job characteristics, length of entrepreneurial experience, and details about entrepreneurial exit.